POST-TRAUMATIC STRESS DISSORDER OF MAIN CHARACTER IN EVERY THING WILL BE FINE MOVIE DIRECTED BY WIM WENDERS - Sakinatun Sakinatun; Tati Mardewi; Furi Indriyani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Literature is a record of human life experience either his or her own experience or others. There are three genres of literature, fiction, non-fiction, and poetry. The movie is included in fiction genre. Movie is one of the most popular fiction. The purpose of movie is to entertain the audience and to be able to take positive lessons from movie. The writer focuses on post-traumatic stress disorder of main character in Every Thing Will Be Fine movie. In Every Thing Will Be Fine movie tells about main character of Tomas Eldan. Descriptive qualitative method is used in this research. In analyzing post-traumatic stress dissorder in this movie, the post- traumatic stress disorder is divided into three parts: the types of post-traumatic stress disorder, the causes of post-traumatic stress disorder, and the effect of post-traumatic stress disorder. Before analyzing post-traumatic disorder, it needs to summarize the story and analyze the main character. The results are got from the types, the causes and the effect of post- traumatic stress disorder that happened to the main character of this movie, Tomas Eldan. All parts of post-traumatic stress disorder can be seen after the main character got the accident that occurred while he was driving and waiting twelve years examining the effect of the tragedy on his life and traumatized him. So the post-traumatic stress disorder is happened in this movie, such as self-injury, suicidal thoughts and behaviors, alcoholic use, and depression.